Association Between Periodontal Health Knowledge and Oral Hygiene in Brazilian Adolescents - Gisele Marchetti; Fabian Calixto Fraiz; Giselle Emilãine da Silva Reis; Joana Leticia Vendruscolo; Luciana Reichert da Silva Assunção (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the influence of oral health knowledge in adolescents' oral hygiene pattern. Material and Methods: Cross-sectional study involving 291 participants aged between 14 and 19 years old enrolled in a public school in Curitiba, Brazil. A self-administered questionnaire containing five affirmations about periodontal diseases and their forms of prevention was arranged on a three-point Likert scale. Correct answers were given a weight=1 and incorrect ones, weight=0. The knowledge score (KS) was determined by the sum. Socioeconomic and demographic data were obtained by a questionnaire sent to those responsible. The oral hygiene pattern was evaluated through the simplified oral hygiene index (OHI-S) by a calibrated researcher (K=0.89). Mann-Whitney U test and univariate and multivariate Poisson regression with robust variance were used for data analysis (α=0.05). Results: There was an inversely proportional association between KS and OHI-S (p=0.018). The multiple model showed that adolescents with a lower KS (PR = 0.93, CI95%: 0.88-0.99), male gender (PR = 1.17, CI95%: 1.01-1.37) and whose caregivers presented a lower level of education (PR=1.30, CI95%: 1.03-1.64) showed a higher index of dental plaque. Conclusion: The level of oral health knowledge, the gender and the caregivers' level of education influences the adolescents' oral hygiene pattern.